Significantly enhanced energy storage performance in BiFeO3/BaTiO3/BiFeO3 sandwich-structured films through crystallinity regulation. Issue 34 (21st August 2018) - Hou, Yafei; Han, Renlu; Li, Weiping; Luo, Laihui; Fei, Weidong
Abstract : By rational design of dielectric contrast, both excellent discharge energy density and efficiency could be simultaneously obtained in sandwich-structured films. Abstract : With the increasing demand of high energy density dielectric films, macrostructure design, for instance the construction of sandwich-structured films, has been attracting much attention due to its promise in raising the discharge energy density along with an enhanced electric breakdown strength. However, the contrast of dielectric constants between neighboring layers plays a dominate role in the distribution of the electric field, which might decrease the electric breakdown strength, and has attracted little attention up to now. Additionally, high energy storage efficiency with low energy dissipation should also be considered for dielectric applications despite enhancing the discharge energy density. In this study, the effects of dielectric constant contrast between neighboring layers have been proposed and investigated in the BiFeO3 /BaTiO3 /BiFeO3 sandwich-structured films through regulating the annealing temperature, in which the polarization behavior has also been tuned by partially crystallizing BiFeO3 and BaTiO3 films. As a result, the BiFeO3 /BaTiO3 /BiFeO3 sandwich-structured film annealed at 550 °C exhibits a favorable discharge energy density of 18.5 J cm −3 and a high energy storage efficiency of 82.3%, which result from the synergetic effect of the polarization behavior ( P m − P r = 12.1 μC cm −2 ) and enhanced electric breakdown strength ( E BDS = 2320 kV cm −1 ). By rational design of the dielectric and ferroelectric properties of individual layers, both excellent discharge energy density and energy storage efficiency could be simultaneously obtained in the sandwich-structured films.